The Effect of Social Media Marketing on Purchase Decision with Brand Awareness as Mediation on Haroo Table - Angelyn Angelyn; David Sukardi Kodrat (Universitas Ciputra Surabaya, 2021)
Haroo Table is an online bakery shop in Surabaya. Haroo Table’s promotional activities turns out is not enough to make company become the first choice because of competitors that has higher brand awareness. The purpose of this research is to find out the effect of social media marketing on purchasing decisions with brand awareness as mediation on Haroo Table. The population in this research is 112 people who following Haroo Table's Instagram and make transaction at least once. The sample that is taken for this research is 88 respondents with purposive sampling method and Slovin. Primary data collection technique is like questionnaires with Likert Scale and secondary data is like internal company data, competitor data and related literature. Data analysis technique uses SEM-PLS. Based on the results of the analysis, it is found that (1) social media marketing has a significant positive effect on Haroo Table brand awareness, (2) social media marketing has a significant positive influence on Haroo Table’s purchase decisions, (3) brand awareness has a significant positive influence on Haroo Table’s purchase decisions and (4) brand awareness can mediate the effect of social media marketing on Haroo Table’s purchase decision.